Pengaruh Pemuridan terhadap Kedewasaan Rohani dan Kaderisasi Pemimpin Gereja - Ivone Sri Wengkau; Ester Yunita Dewi; Maria Titik Windarti (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to determine the effect of discipleship on the spiritual maturity of God's servants and the regeneration of church leaders. The study uses a quantitative method with a correlational design. The results showed that discipleship had a positive and significant effect on the spiritual maturity of ministers. Ministers who were actively and consistently involved in discipleship showed more mature faith, stronger Christian character, high commitment to ministry, and more stable spiritual discipline. In addition, discipleship was also proven to have an effect on the regeneration of church leaders. God's servants who were trained through structured discipleship were better prepared to take on leadership roles, both in terms of ministry responsibilities, exemplary lives, and the ability to mentor others. These findings confirm that discipleship is not merely a routine spiritual training activity, but a strategic means of forming ministers who are spiritually mature and ready to become church leaders.